FIR implementation of the Steady-State Kalman Filter. (29th June 2009) - Assimakis, Nicholas; Adam, Maria
In this paper, an FIR implementation for the Steady-State Kalman Filter (SSKF) is proposed. The method requires the knowledge of a subset of previous time measurements. The proposed algorithm is faster than the classical one, especially for large estimation time. The proposed implementation is also applicable to periodic models.